Samuel Beckett dans les marges du surréalisme : - Posse, Bernard-Olivier (BRILL, 2022)
Longuement, la question de la productivité du mouvement surréaliste français sur l'œuvre de Samuel Beckett fut débattue, polarisée entre rejet et acceptation péremptoire. Cette possible influence trouve un point d'appui important dans Samuel Beckett dans les marges du surréalisme , découvrant une œuvre faite de reprises et d'emprunts de la poésie surréaliste. Par un dépouillement attentif des archives beckettiennes incluant correspondance, cahiers préparatoires et publications en revue, Bernard-Olivier Posse propose une méthode philologique mêlant analyse littéraire et perspective sociologique propice à reconsidérer la posture auctoriale de Samuel Beckett. The question of how influential the French surrealist movement has been on the work of Samuel Beckett has been debated for a long time but the answers were only made of peremptory oppositions : either rejection or acceptation. Samuel Beckett dans les marges du surréalisme aims to demonstrate the (ambiguous) way Beckett works with surrealist poetry by a play of quotations which are always repeated, always altered. Based on research on Beckettian archives such as his correspondence, preparatory notes and publications in journals, this book combines literary analysis and sociological perspective in order to understand how Beckett deals with his self-representation as a writer.
10.1163/9789004467392
Keywords: Literary criticism.; Beckett; Samuel; Literature & literary studies; Literature: history & criticism; French poetry.; Surrealism (Literature)